Microstructure and mechanical properties of an Al‐Si alloy reinforced by Al64Cu24Fe12 quasi‐crystalline particles: Gefüge‐ und mechanische Eigenschaften einer mit Al64Cu24Fe12 quasi‐kristallinen Partikeln verstärkten AlSi‐Legierung. Issue 2 (20th February 2018) - Wang, Y.F.; Hou, H.; Zhao, Y.H.; Tian, J.Z.
Abstract: In this work, aluminum‐silicon alloy reinforced with Al64 Cu24 Fe12 quasi‐crystalline particles have been prepared by a traditional casting method with proper heat treatment process. The microstructures of the composites were examined using optical microscopy, scanning, X‐ray and energy dispersive spectrometer. The results indicate that there was no quasi‐crystalline phase remained and a new phase‐β (Al65‐75 Si13‐26 Fe3‐10 ) phase formed, which may act as a new reinforcing phase. There are three primary phases in the final composite: eutectic silicon, β‐phase and the α‐aluminum phase. Also the changes of mechanical properties were studied by tensile test and Vickers hardness test. The test results demonstrate that the mechanical properties of the composite is remarkably improved by adding proper amount of quasi‐crystalline particles. After adding 7.70 vol.% quasi‐crystalline particles, the tensile strength and the hardness increased by 70 % and 62 % respectively. However, adding a big amount (10.09 vol.%) of particles to molten aluminum‐silicon alloy will cause the particles aggregation and adhesion, which resulted in the decrease of the mechanical properties.